Monitoring Korosi Discharge Conveyor F pada Tambang Batubara PT XYZ di Kabupaten Merangin Provinsi Jambi - Muhammad Rizky Picauly; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyors are the most widely used means of transporting raw materials in the mining industry, which are used to move excavated materials from the previous location to the next location, such as a stockpile. The conveyor structure used is made of carbon steel which is susceptible to corrosion. This research was conducted on the structure conveyor along 114 meters divided into 3 segments with 25 test points. This study aims to determine the type of corrosion, corrosion control, corrosion rate and the remaining life of the structure conveyor. The research was conducted on a 114 meter long conveyor structure which was divided into 3 segments and 25 test points, with a service life of 7 years and a design life of 15 years. The research methodology is the measurement of the thickness reduction of the conveyor structure. The actual thickness has a value ranging from 7.66-12.19mm measured with the Ultrasonic Thickness Gauge TT 130. Environmental data is in the form of rainfall data for 2015- 2019 with an average of 236.83 mm/year, average air temperature of 27.83°C and an average relative humidity of 85.60 %. The type of corrosion that occurs in the structure conveyor is uniform corrosion. The corrosion control method applied to the conveyor structure is the coating method with a primer coating Seaguard 5000, Intermediate coating Sherglass FF and top coating Aliphatic acrylic modified polyurethane. The corrosion rate of the structure conveyor ranges from 0.186-0.334 mm/year. Abstrak. Conveyor merupakan alat angkut raw material yang paling banyak dipakai di industri pertambangan yang digunakan untuk memindahkan material bahan galian dari tempat sebelumnya ke tempatnya selanjutnya seperti stockpile. Struktur conveyor yang digunakan adalah berbahan dasar baja karbon yang rentan terhadap korosi. Tujuan penelitian ini adalah untuk mengetahui jenis korosi, metode pengendalian korosi, laju korosi dan sisa umur pakai struktur conveyor. Penelitian dilakukan pada struktur conveyor sepanjang 114 meter yang dibagi menjadi 3 segmen dan 25 test point, dengan umur pakai 7 tahun dan umur desain 15 tahun. Metodologi penelitian adalah pengukuran pengurangan ketebalan struktur conveyor. Tebal aktual mempunyai nilai berkisar 7,66-12,19mm diukur dengan alat ukur Ultrasonic Thickness Gauge TT 130. Data lingkungan berupa data curah hujan tahun 2015-2019 dengan rata-rata 236,83 mm/tahun, suhu udara rata-rata 27,83 C dan kelembaban relatif rata-rata 85,60 %. Pada penelitian ini jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode perlapisan ini menggunakan sistem 3 lapisan anti korosi yang terdiri dari lapisan primer Seaguard 5000, lapisan antara Sherglass FF dan lapisan atas Aliphatic acrylic modified polyurethane. Laju korosi struktur conveyor yaitu 0,186-0,334 mm/tahun.